2015
DOI: 10.1371/journal.pone.0131658
|View full text |Cite
|
Sign up to set email alerts
|

Serum Cell Death Biomarkers for Prediction of Liver Fibrosis and Poor Prognosis in Primary Biliary Cirrhosis

Abstract: The development of simple, noninvasive markers of liver fibrosis is urgently needed for primary biliary cirrhosis (PBC). This study examined the ability of several serum biomarkers of cell death to estimate fibrosis and prognosis in PBC. A cohort of 130 patients with biopsy-proven PBC and 90 healthy subjects were enrolled. We assessed the utility of the M30 ELISA, which detects caspase-cleaved cytokeratin-18 (CK-18) fragments and is representative of apoptotic cell death, as well as the M65 and newly developed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…In contrast in patients with decompensated cirrhosis, the additional benefit of M65EpiDeath for risk prediction was much lower. A similar prognostic role of M65EpiDeath has been recently reported by a study performed in patients with primary biliary cirrhosis (16). According to our study, M65EpiDeath was a predictor of death and decompensation (16).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast in patients with decompensated cirrhosis, the additional benefit of M65EpiDeath for risk prediction was much lower. A similar prognostic role of M65EpiDeath has been recently reported by a study performed in patients with primary biliary cirrhosis (16). According to our study, M65EpiDeath was a predictor of death and decompensation (16).…”
Section: Discussionsupporting
confidence: 92%
“…A similar prognostic role of M65EpiDeath has been recently reported by a study performed in patients with primary biliary cirrhosis . According to our study, M65EpiDeath was a predictor of death and decompensation . High levels of M30 and M65 were also found in another cholestatic liver disease, namely primary sclerosing cholangitis, and the parameters M30 and M65 were associated with more advanced disease .…”
Section: Discussionsupporting
confidence: 91%
“…Markers of cell death, in particular, caspase‐cleaved keratin 18 (cK18) and keratin 18 (K18), have been previously demonstrated to be clinically relevant in the diagnosis, assessment of disease severity, and prognosis of a wide range of acute and chronic liver diseases, including chronic and acute on chronic hepatitis B, chronic hepatitis C, drug‐induced liver injury, nonalcoholic fatty liver disease, alcoholic hepatitis (AH), acute liver failure, and primary biliary cirrhosis (reviewed in http://onlinelibrary.wiley.com/doi/10.1002/hep.29581/suppinfo), as well as in nonhepatological diseases such as breast and gastrointestinal (GI) cancer and sepsis . Keratins are the main epithelial subgroup of intermediate filament (IF) proteins .…”
mentioning
confidence: 99%
“…Given that cirrhosis is an end‐stage liver disease and patients with cirrhosis generally have a poor prognosis, the long‐term outcome of patients with PBC was predicted only by Scheuer stage 3 and Nakanuma fibrosis score 2, which together were referred to as significant portal–bridging fibrosis. The prognosis of patients with PBC appears to be dictated by the presence and extent of fibrosis in liver biopsy findings . The long‐term outcome of patients with PBC could also be independently predicted by histological features, including fibrosis .…”
Section: Discussionmentioning
confidence: 99%
“…The prognosis of patients with PBC appears to be dictated by the presence and extent of fibrosis in liver biopsy findings. 26 The long-term outcome of patients with PBC could also be independently predicted by histological features, including fibrosis. 5 In contrast, Kumagi et al revealed that the baseline severity of BDL is associated with histological progression as well as biochemical response to UDCA.…”
Section: P-values Represent Comparisons Between Responders and Non-rementioning
confidence: 99%